Public private partnership (APP) experiences Cundinamarca (2014)
APP are a tool to attract private capital, which is embodied in a contract between a state agency and a natural or legal person of private law, for the provision of public goods and related services , which involves the retention and transfer , risks between the parties and payment mechanisms , related to the availability and level of service infrastructure and / or service. Given the above, the Cundinamarca through the Institute for Infrastructure and Concessions Cape - ICCU develops a project to rehabilitate the road Sibaté - Fusagasugá - Pasca by APP scheme , constitutes a valuable tool for achieving the objectives , as it is an alternative that allows the state to find additional sources of national budget resources , and facilitate project implementation and growth development. The drawbacks presented in the road infrastructure, the provinces of Soacha and Sumapaz has forced the community to use alternative ways to communicate and market their products , which represent a major time and cost them more expensive , this project aims to attract government back to all users of this region to the departmental roads and provide greater economy in the marketing of their products. Following this issue the ICCU has developed a PPP project in the aforementioned corridor , which aims to reduce the travel time between Sibaté - Fusagasugá - Pasca , for farmers and industries in the region take advantage of the walkability of their products the different municipalities , cities and departments. According to the characteristics of the affected area, is performed by a base geopolitical division benefited stakeholders with the implementation of this project as well : • Conveyor • Agricultural Sector • Livestock Sector • Mayors • Citizen oversight committees • Near Town Through this scheme the private sector APP can design, build, finance , infrastructure required for the rehabilitation and improvement of satellite Sibaté - Fusagasugá - Pasca and take over management of maintenance and operation for the duration of the contract without problems in the availability resource . The project aims to create a number of direct and indirect jobs in nearby towns , through which several families will provide coverage of basic needs and in general all the benefits of development involves the improvement of a road . The involvement of private capital in the development of public infrastructure projects is a theme already developed in Colombia , The Constitution enacted in 1991 , opened new spaces for private participation in state projects , then the laws and decrees are set required in the contract with the State: Law 80 of 93, by which the General Contracting of Public Administration is issued Act 1150 of 2007. Through which measures efficiency and transparency in Act 80 of 1993 are introduced and other general provisions on contracting with Public Resources dictate . With the APP schema , generated competition in technology and quality within the private sector companies , which favors the technical conditions for the implementation of the project and getting a premium product for users. The area where the work would be done , now no major risks in terms of groups outside the law. The only factor that could affect the safety is when some kind of protest submitted by farmers and transporters that hinder and / or attempt against equipment, material and personnel . In this case we have the support of the military. At baseline is aimed to answer the question , What would be the economic impact of the population, the highway stretch Sibaté - Fusagasugá, Pasca , Colombia Cundinamarca Department , if you get to create a PPP in this corridor ? , with the study concluded that by generating a PPP corridor already mentioned , the economic impact is positive reckoned that tourism would increase and farmers and industries in the region can take advantage of the walkability of their products to various municipalities , cities and departments. Could analyze investment opportunities through the PPP scheme the private sector to design, build, finance , infrastructure via Sibaté - Fusagasugá - Pasca , which according to the financial model studied are feasible and generate a large long term profitability , which is the purpose of the proposed APP with 100% private capital . Following infrastructure problems it was observed that the background of the situation or problem of which the PPP in the road corridor Sibaté - Fusagasugá - Pasca in Cundinamarca Colombia , is the poor state of the road, as this has faults and shows lack of rehabilitation , although the ICCU invests in construction and maintenance of the corridor is not enough to provide the inhabitants and road users sufficient quality and security they require .